Leading Virtual Project Teams Adapting Leadership Theories and Communications Techniques to 21st Century Organizations. - Lee, Margaret R. (Milton : Auerbach Publishers, Incorporated, 2021)
The second decade of the 21st century brought unprecedented challenges to traditional workplaces forcing the advance of working from home (telework) due to a global virus pandemic. Individuals with little or no background or training in e-leadership, virtual project management, or virtual team management suddenly found themselves in the environment of virtual work. Leading Virtual Project Teams, Second Edition addresses the challenges that today's virtual project management environment poses to traditional methods of leadership and communication. Leadership for successful virtual team management is different from traditional, collocated project team management. Being familiar with appropriate e-leadership styles for virtual project teams and the transition toward new leadership styles, communication techniques for virtual project teams, and e-leadership competencies is an important part of managing projects and human resources in successful organizations today. The second edition also examines: Virtual meeting techniques Inclusive language Managing virtual relationships Why virtual work is now more important The work-at-home environment By recognizing how virtual teams are different from traditional teams, those managing virtual projects may be able to offer benefits to their organization by providing positive, successful leadership and exceptional communications, resulting in better project deliverables and products. This book provides an approach that explores all facets of e-leadership--from how traditional leadership theories and models can be applied by 21st century leaders to providing methods by which the virtual project manager can enhance virtual project communications to meet the needs of our modern global business world. It features project management checklists and templates and includes business cases, best practices, and tools and techniques for virtual project management communications.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Project management; Virtual work teams -- Management; Teams in the workplace; BUSINESS & ECONOMICS / Project Management; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Leadership